The Employment Effects of State Hiring Credits - David Neumark; Diego Grijalva (Institute for the Study of Labor (IZA), 2015)
State and federal policymakers grappling with the aftermath of the Great Recession sought ways to spur job creation, in many cases adopting hiring credits to encourage employers to create new jobs. However, there is virtually no evidence on the effects of these kinds of counter-recessionary hiring credits the only evidence coming from much earlier studies of the federal New Jobs Tax Credit in the 1970s. This paper provides evidence on the effects of state hiring credits on job growth. For many of the types of hiring credits we examine we do not find positive effects on job growth. However, some specific types of hiring credits most notably including those targeting the unemployed, those that allow states to recapture credits when job creation goals are not met, and refundable hiring credits appear to have succeeded in boosting job growth, more so during the Great Recession period or perhaps recessions generally. At the same time, some credits appear to generate hiring without increasing employment or to generate much more hiring than net employment growth, consistent with these credits leading to churning of employees that raises the costs of producing jobs via hiring credits.
Keywords: J23; 330; labor demand; hiring credits; employment growth